Social dynamics through kinetic exchange: the BChS model - Biswas, Soumyajyoti; Chatterjee, Arnab; Sen, Parongama; Mukherjee, Sudip; Chakrabarti, Bikas K. (Frontiers in Physics, 2023)
This review presents an overview of the current research in kinetic exchange models for opinion formation in a society. The review begins with a brief introduction to previous models and subsequently provides an in-depth discussion of the progress achieved in the Biswas-Chatterjee-Sen model proposed in 2012, also known as the BChS model in some later research publications. The unique feature of the model is its inclusion of negative interaction between agents. The review covers various topics, including phase transitions between different opinion states, critical behavior dependent on various parameters, and applications in realistic scenarios such as the United States presidential election and Brexit.